Differential response of Trichloris ecotypes from different habitats to drought and salt stress - Marinoni, Lorena del Rosario (2020)
Native plant genetic resources have evolved from long processes of natural selection and adaptation to specific environments, and have developed tolerance to various stresses prevailing in their natural habitats via adaptive morphophysiological features. The associations between environmental stress conditions (aridity degree and salinity) prevailing in the original habitat of Argentine native Trichloris species (T. crinita and T. pluriflora) and various biometric and physiological traits were evaluated. Trials were carried out in hydroponics in a growth chamber. Components of initial plant growth, oxidative stress expression and antioxidant activity under drought and salt stress were measured in ecotypes of both species, as well as Na+ and K+ leaf tissue concentration and excretion rates under salinity. Ecotypes from arid and semiarid origin of both species had higher drought tolerance. Regarding salt stress, T. crinita ecotype from alkali soil showed stimulated growth under salinity and an ecotype from saline soil kept high root and shoot biomass production. Although the ecotypes of T. pluriflora were not significantly salt-sensitive, none stood out. Many active salt glands on the abaxial leaf surface, high Na/K excretion ratio and high leaf tissue concentration of sodium were found for salt-tolerant ecotypes. This study identified ecotypes with tolerance to prevailing stressful conditions of natural habitat of native forage species to be introduced to plant breeding programmes for restorations purposes. Trichloris pluriflora is an unexplored genetic resource for semiarid rangeland, thus this study is the first report of drought tolerant ecotypes.